Analysis of Abu Hanifah’s Opinion on the Sale of Sacrificial Animal Skins - Muhamad Jamal; Andi Susanto; Mohammed Hafiz Ali Wafa (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
This study aims to examine the views of Islamic jurists regarding the ruling on selling the hide of sacrificial animals and to analyze Abu Hanifah’s opinion in relation to the practice of selling sacrificial animal hides in Lowungu Village, Bejen District, Temanggung Regency. This research employs a qualitative descriptive method, and data were collected through direct interviews with informants involved in the implementation of the sacrificial slaughter. The findings reveal two principal views in Islamic jurisprudence concerning the sale of sacrificial animal hides. Some scholars such as Abu Hanifah, Atho', al-Awza‘i, Ahmad, Ishaq, Abu Thaur, and one opinion within the Shafi‘i school permit the sale of the hide of sacrificial animals, provided that the proceeds are distributed to the beneficiaries (mustahik) of the sacrifice. The Hanafi school also allows the hide and internal parts of the sacrificial animal to be exchanged for items that bring greater benefit to the recipients. In contrast, scholars from the Maliki, Hanbali, and Shafi‘i schools, including Imam Nawawi, hold that selling the hide of sacrificial animals is not permissible. Meanwhile, the sacrificial committee in Lowungu Village sells the hides due to practical considerations, such as the absence of community members capable of processing them, which may lead to neglect, damage, or waste. The proceeds from the sale are used to support the operational needs of the sacrificial activities, including purchasing plastic bags, committee consumption, and allocating a portion for the mosque’s funds.